The Influence Of Perception Of Price And Pacilities On Consumer Statisfaction Of Mini Soccer Indosoccernesia In Tasikmalaya City - Jamal Saepul Mi’raj; Arga Sutrisna; Depy Muhamad Pauzy (Journal of Indonesian Management, 2022)
The purpose of this study was to determine the effect of perception of price and pacilities simultaneously or partially on consumer statisfaction of Mini Soccer Indosoccernesia in Tasikmalaya City. Survey of Indosoccernesia consumers in Tasikmalaya City. The research method used is descriptive and verification method. The sample in this study amounted to 100 respondents. Data collection was carried out using a questionnaire. The data analysis used is multiple regression analysis. The results of this study indicate that perception of price and pacilities simultaneously have a significant effect on consumer statisfaction. Partially, perception of price has a significant effect on consumer statisfaction. Partially, the pacilities has a significant effect on consumer statisfaction.